Evaluation of PD-L1/PD-1 on circulating tumor cells in patients with advanced non-small cell lung cancer. (12th January 2018) - Kallergi, Galatea; Vetsika, Eleni-Kyriaki; Aggouraki, Despoina; Lagoudaki, Eleni; Koutsopoulos, Anastasios; Koinis, Filippos; Katsarlinos, Panagiotis; Trypaki, Maria; Messaritakis, Ippokratis; Stournaras, Christos; Georgoulias, Vassilis; Kotsakis, Athanasios
Background: Circulating tumor cells (CTCs) could escape from the immune system through the programmed death-ligand 1 (PD-L1)/programmed cell death protein 1 (PD-1) axis leading to the development of metastasis. The current study investigated the expression of PD-1/PD-L1 on CTCs isolated from non-small cell lung cancer (NSCLC) patients treated with chemotherapy. Patients and methods: CTCs were isolated from 30 chemo-naïve stage IV NSCLC patients before and after front-line chemotherapy using the ISET filtration platform. CTCs were detected by Giemsa and immunofluorescence (IF) staining. Samples were analyzed with the ARIOL system. Results: Giemsa staining revealed that 28 (93.3%) out of 30 and 9 (81.8%) out of 11 patients had detectable CTCs at baseline and after the third chemotherapy cycle, respectively. Cytokeratin (CK)+/CD45- CTCs by IF could be detected in 17 of 30 (56.7%) patients at baseline and in 8 of 11 (72.7%) after the third chemotherapy cycle. Spearman analysis revealed a significant correlation ( p = 0.001) between Giemsa-positive and IF-positive (CK+/CD45-) CTCs. At baseline, PD-1 and PD-L1 expression was observed in 53% and in 47% CK-positive patients, respectively. After the third treatment cycle the corresponding numbers were 13% and 63% respectively. Median progression-free survival (PFS) was significantly shorter in patients with >3 PD-1(+) CTCs at baseline compared with those with <3 PD-1(+) CTCs ( p = 0.022) as well as in patients with >1 Giemsa-positive tumor cells ( p = 0.025). Conclusion: PD-1(+) and PD-L1(+) CTCs could be detected before and after front-line chemotherapy in patients with metastatic NSCLC. The presence of high PD-1(+) CTC numbers before treatment is associated with a poor patient clinical outcome.